sistem informasi Sistem Informasi Penilaian Kinerja Pegawai di SETDA Bagian Umum Kabupaten Situbondo - Zaehol Fatah; Maharani Rahmatul Hanani (Pusat Riset dan Inovasi Nasional, 2025)
Employee performance appraisal is a crucial aspect of human resource management in government agencies. At SETDA General Affairs Section in Situbondo Regency, the manual performance appraisal system faces several challenges including time inefficiency, prone to recording errors, and lack of transparency in the assessment process. This study aims to design and develop an Employee Performance Appraisal Information System to overcome these problems and improve efficiency, accuracy, and transparency. The research methodology uses SDLC Waterfall with stages of system analysis, design, implementation, testing, and maintenance. Data collection was conducted through observation, interviews with employees and management, and literature study. The system was developed as a web-based application featuring employee data management, performance criteria input (work quality, work quantity, discipline, initiative, and teamwork), automatic calculation, and real-time reporting. Implementation results show that the system successfully simplifies the performance appraisal workflow, improves data accuracy, provides faster and more transparent reports, and supports quicker decision-making for employee development, promotions, incentives, and public service quality improvement at SETDA General Affairs Section in Situbondo Regency.